Etika dagang islam: perspektif kejujuran dalam al-qur’an dan hadis - Kartika, Adhisti Malla (Maliki Interdisciplinary Journal, 2025)
Successful trading is not only a matter of getting a lot of profit, but also blessings and prosperity for the surroundings. The religion of Islam teaches every trader to be honest and fair in trading. Through the study of the verses of the Quran, such as QS Al-Mutaffifin and QS Al-An'am, as well as the hadiths of the prophet, it is explained that a Muslim is required to have honest and fair principles in trading, not to commit fraud in it. In this article, the author uses the study of literature to examine various religious literature to describe how the Qur'an and hadith can provide guidance in implementing the principles of honesty and fairness in buying and selling activities. The results of the discussion refer to the importance of being honest in trading, criticism for traders who cheat in weighing and scaling. With a complete understanding of honesty in trading, it is hoped that Muslims can apply the principles of honesty and fairness in trading and stay away from fraudulent attitudes in trading in order to trade to get blessings and prosperity from Allah.